Design of a Web-Based Jambi City Civil Service Police Unit Member Activity Reporting System - Rian Saputra; Hendrawan; Muhammad Ismail (MASE - Media Applied and Engineering, 2026)
Currently, all operational activities in the Jambi City Civil Service Police Unit are carried out manually, and the existing computers are only used to make reports. These operational activities include the process of entering member data, inputting activity reports, and also managing information about the unit. With manual data collection, it requires a lot of labor to carry out repetitive administrative tasks. The aim of this research is to analyze the needs for an activity reporting system for members of the Jambi City Civil Service Police Unit and to design a website-based activity reporting system for members of the Jambi City Civil Service Police Unit. Researchers carried out system development using the Waterfall method. The results of this research. With a new system designed to make it easier to collect data on reports on the activities of the Jambi City Civil Service Police Unit quickly and the data is stored well, in addition to shortening the time for making reports.